A suspensão da ética mediante a fé em Kierkegaard: uma análise da relação entre fé e ética em “Temor e Tremor” - Alves, Ítina Fernandes Silva (2023)
This research delves into the theme of faith in the work "Fear and Trembling" by Danish philosopher Søren Kierkegaard, authored under one of his pseudonyms, Johannes de Silentio. The central focus of the work revolves around the story of Abraham, embodying the knight of faith. The author explores the unfolding of the patriarch's existence and identifies defining characteristics of faith. Thus, this study proceeds by initially elucidating a foundational concept in Kierkegaard's thought: anguish. For Kierkegaard, anguish is present in the journey of the knight of faith from start to finish. Building upon the insights derived from this work, we will focus on highlighting faith and its paradoxical nature—the faith as absurdity and faith as passion. These three aspects will serve as a basis for understanding the concept of faith and subsequently highlight the divergence faith maintains from any rational stance. In light of this distinction, we will observe the limits of ethics in the face of faith, and therefore of the reason itself. These boundaries, as reflected and presented by Kierkegaard, invite contemplation of Abraham's life as supremely paradoxical, rather than that of a murderer. Through what Kierkegaard called the teleological suspension of the ethical, we will conclude that faith is this paradox that allows the Individual to step back from the general and elevate themselves above it. This trajectory will make it possible to differentiate the knight of faith from the tragic hero, as the latter remains within the general and is understood through ethics. In contrast, the former transcends it, with actions grounded solely in faith rather than morality. Finally, it is observed that the Individual has an absolute duty to God, which absolves them from fulfilling their moral duty when it becomes a temptation to forsake their higher duty. Thus, we encounter a mode of existence that goes beyond the ethical stage—a life of faith that supersedes the former by transcending all moral obligations. This is why Abraham is saved from condemnation as a potential murderer and acknowledged as the father of faith